Darurah (Absolute Necessity) and Rukhsah (Concession) in Islamic Law - Zulbaidah, Zulbaidah (International Journal of Nusantara Islam, 2018)
This article discusses about darurah (absolute necessity) and rukhsah (concession) in Islamic law. In a darurah (absolute necessity) condition a person is allowed to take rukhsah (concession) law. This is the relief given by Allah as the maker of the law to be able to forgive both in the form of carrying out something which is prohibited or in the form of leaving something ordered. Like eating a carcass in a forced state when someone does not find halal food, and leaves fasting for a sick person. In this case a person may move from a general legal provision called ‘azimah, and move to the lightening law called rukhshah. Therefore, darurah is closely related to rukhshah, because darurah is not a law but leaves the law. Darurah is a trait that allows mukallaf to leave ‘azhimah and take the rukhshah law, provided that it is measured according to the size of the darurah.